Air Compression Cycle Analysis in Mines - Awatef Wahid Nasra (Tishreen University, 2020)
This work analyzes the logic cycle of air compression in mining compressors and their logic, how to reduce the work done on compression, increase the yield, and how to optimize the method of compression through the narrowing of a double compressive cycle. This has significantly improved the quality of air produced and reduced energy loss in the air network by reducing the temperature of the compressed gas produced. An increase in the weight of the compressor was obtained, which enables it to be used at a high altitude above sea level in addition to saving the compressor. يتم في هذا العمل تحليل دورة انضغاط الهواء في الضواغط المنجمية ومنطقيتها، وكيفية تخفيض العمل المبذول على الانضغاط، وزيادة المردود، وتحقيق الأسلوب المثالي للانضغاط وذلك من خلال تطبيق دورة ثنائية للانضغاط. إن تطبيق هذه الطريقة سمح بتحسين نوعية الهواء الناتج بشكل كبير كما أنها خفضت ضياع الطاقة في الشبكة الهوائية عن طريق تخفيض درجة حرارة الغاز المضغوط الناتج. كما تمّ الحصول على زيادة في الإنتاجية الوزنية للضاغط مما يمكن من استخدامه على ارتفاع عال عن سطح البحر بالإضافة إلى توفير في عمل الضاغط.